2015
DOI: 10.1016/j.gca.2015.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Uranium isotopic compositions of the crust and ocean: Age corrections, U budget and global extent of modern anoxia

Abstract: The 238 U/ 235 U isotopic composition of uranium in seawater can provide important insights into the modern U budget of the oceans. Using the double spike technique and a new data reduction method, we analyzed an array of seawater samples and 41 geostandards covering a broad range of geological settings relevant to low and high temperature geochemistry. Analyses of 18 seawater samples from geographically diverse sites from the Atlantic and Pacific oceans, Mediterranean Sea, Gulf of Mexico, Persian Gulf, and En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
201
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(224 citation statements)
references
References 131 publications
(293 reference statements)
20
201
0
3
Order By: Relevance
“…Virginia Polytechnic Institute and State University, Blacksburg, USA a globally integrated scale. This is possible due to the long residence time and uniform δ 238 U of uranium in the modern ocean and predicted for the Cambrian ocean (Weyer et al, 2008;Dahl et al, 2014;Tissot and Dauphas, 2015). The δ 238 U proxy has been utilised to track past global ocean redox during three known oceanic anoxic events (Montoya-Pino et al, 2010;Brennecka et al, 2011;Dahl et al, 2014;Elrick et al, 2016;Lau et al, 2016), where anoxic water masses expanded over larger areas of the seafloor and caused negative δ 238 U excursions.…”
Section: Lettermentioning
confidence: 99%
See 2 more Smart Citations
“…Virginia Polytechnic Institute and State University, Blacksburg, USA a globally integrated scale. This is possible due to the long residence time and uniform δ 238 U of uranium in the modern ocean and predicted for the Cambrian ocean (Weyer et al, 2008;Dahl et al, 2014;Tissot and Dauphas, 2015). The δ 238 U proxy has been utilised to track past global ocean redox during three known oceanic anoxic events (Montoya-Pino et al, 2010;Brennecka et al, 2011;Dahl et al, 2014;Elrick et al, 2016;Lau et al, 2016), where anoxic water masses expanded over larger areas of the seafloor and caused negative δ 238 U excursions.…”
Section: Lettermentioning
confidence: 99%
“…This excursion serves as an important stratigraphic marker, although little is known about the biogeochemical significance of the event. The end-Stage 2 samples carry low δ 238 U values of -0.65 ‰, increasing stratigraphically to a value of -0.45 ‰ that approaches the modern oxygenated oceans, -0.39 ± 0.01 ‰ (Tissot and Dauphas, 2015), before again returning in two steps to -0.7 ‰. This positive δ 238 U excursion of +0.25 ‰ coincides with the positive carbon isotope excursion, suggesting that they are both linked to the changes in global seawater chemistry.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Goldmann et al (2015) found the Pb-Pb ages they dated are 0.9 Ma younger than the age determined with previously assumed value 137.88 for 238 U/ 235 U. Tissot and Dauphas (2015) proposed equations for the corrections on Pb-Pb and U-Pb ages, although these corrections are much smaller than the ages of the samples. The magnitude and direction of Pb-Pb and U-Pb age corrections are only related to a sample's age and 238 U/ 235 U ratio.…”
Section: Isotope Geochronologymentioning
confidence: 69%
“…Nowadays, a few researches have verified that 238 U/ 235 U is not invariable (Stirling et al 2007;Weyer et al 2008;Hiess et al 2012;Goldmann et al 2015;Tissot and Dauphas 2015). Therefore, an age correction is required if the value of 137.88 ( 238 U/ 235 U ratio) is used for dating.…”
Section: Isotope Geochronologymentioning
confidence: 99%